Answer:
ln(3) + 5 - 3ln(x) or 6.0986 - 3ln(x)
Step-by-step explanation:
[tex]ln(\frac{3e^{5} }{x^3} )[/tex]
[tex]ln(\frac{3e^{5} }{x^3} )[/tex] = [tex]ln(3e^5)-ln(x^3)[/tex], since ln(x/y) = ln(x)-ln(y)
[tex]ln(3e^5)[/tex] = ln(3) + [tex]ln(e^5)[/tex], since ln(xy) = ln(x) + ln(y)
[tex]ln(\frac{3e^{5} }{x^3} )[/tex] = ln(3) + [tex]ln(e^5)-ln(x^3)[/tex]
[tex]ln(\frac{3e^{5} }{x^3} )[/tex] = [tex]ln(3) + 5ln(e) -3ln(x)[/tex], since ln([tex]x^y[/tex]) = yln(x)
[tex]ln(\frac{3e^{5} }{x^3} )[/tex] = ln(3) + 5 -3ln(x) , since ln(e)=1
if needed further simplification,
ln(3) = 1.0986
ln(e) = 1
[tex]ln(\frac{3e^{5} }{x^3} )[/tex] = 6.0986 - 3ln(x)